Eye and Foot Coordination Relationship to Passing and Stopping Football at Uptd Sd Negeri Langkap 02 Burneh - Rijal, Syaiful; Anwar, Khoirul; Handayani, Heni Yuli (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine the relationship between eye-foot coordination and the passing and stopping skills in football at UPTD SD Negeri Langkap 02 Burneh. The research used a descriptive quantitative method with a survey approach. The population consisted of 25 male students aged 10–12 years from grade VI of SDN Langkap 02 Burneh. The instruments used were an eye-foot coordination test and a football passing and stopping skill test. Data analysis was conducted using the Pearson Product Moment correlation formula to determine the strength of the relationship between the two variables. The results showed a significant relationship between eye-foot coordination and the ability to perform passing and stopping. Based on test scores categorized as